GeSn photodetection and electroluminescence devices on Si - Oehme, M.; Kasper, E.; Schulze, J. (ECS Transactions, 2012)
GeSn heterojunction photonic devices with Sn concentration up to 4 % were fabricated. The complete layer structure is grown by means of ultra low temperature MBE with special Ge/Si heterocontacts. The Sn incorporation in Ge is facilitated by a very low temperature growth step in order to suppress Sn surface segregation. For vertical photodetectors an increase of the optical responsivity for higher wavelengths can be observed with increasing Sn content. At the wavelength of 1600 nm the optical responsivity is increased by more than a factor of 10 for the GeSn p-i-n diode with 4 % Sn in comparison to the Ge reference diode. Clear direct bandgap electroluminescence emission at room temperature is demonstrated for LED's with this new material. © The Electrochemical Society.
CRIS-Team Scopus Importer:2021-06-29